2016
DOI: 10.1515/phys-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

Variable Viscosity Effects on Time Dependent Magnetic Nanofluid Flow past a Stretchable Rotating Plate

Abstract: An attempt has been made to describe the effects of geothermal viscosity with viscous dissipation on the three dimensional time dependent boundary layer flow of magnetic nanofluids due to a stretchable rotating plate in the presence of a porous medium. The modelled governing time dependent equations are transformed a from boundary value problem to an initial value problem, and thereafter solved by a fourth order Runge-Kutta method in MAT-LAB with a shooting technique for the initial guess. The influences of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A fourth order Runge-Kutta method is employed to obtain the numerical solution followed by shooting technique with a systematic guessing of missing boundary conditions U′(0),V′(0), and θ′(0) as employed by Ram et al [36].…”
Section: Modelling and Solution Of The Problemmentioning
confidence: 99%
“…A fourth order Runge-Kutta method is employed to obtain the numerical solution followed by shooting technique with a systematic guessing of missing boundary conditions U′(0),V′(0), and θ′(0) as employed by Ram et al [36].…”
Section: Modelling and Solution Of The Problemmentioning
confidence: 99%
“…The results indicated that increasing viscosity variation decreases the radial and axial velocity. Further, Ram et al . (2016) studied variable viscosity effects on time-dependent magnetic nanofluid flow past a stretchable rotating plate.…”
Section: Introductionmentioning
confidence: 96%
“…Their outcomes show that solid volume friction decreases the velocity of nanoparticles close to the wall of the channels and escalates the thickness of the thermal boundary layer of the channels. The study of magnetohydrodynamic flow of nanofluids over a rotating stretchable plate in the presence of a magnetic field was captured by Ram et al [8].…”
Section: Introductionmentioning
confidence: 99%